Laparoscopic Sigmoidectomy: Report of the 7 First Cases Performed in Peru - Bazán, Alejandro (1995)
We present seven cases of laparoscopic sigmoidectomy performed at the Surgical Service N" 3, Department 01' General Surgery, Guillermo Almenara Irigoyen National Hospital between 1993 and 1995. Five had benign pathology (four had dolicomegasigma and one benign villous adenoma) and two presented resectable malignant tumor pathology. We describe the surgical procedures and the usually satisfactory immediate post-operative period.